Intra-abdominal tumour secondary to chronic adnexal torsion - Aparicio López, Daniel (Cirugía del Uruguay, 2021)
A 65-year-old woman who consulted for constitutional syndrome and vomiting of 3 months of evolution. CT identified a solid and heterogeneous 25x19x14cm inframesocolic mass that displaced intestinal loops and mesenteric vessels (Figure 1). The percutaneous biopsy revealed a low-grade mesenchymal tumor indicating surgery. A large necro-hemorrhagic tumor dependent on the left ovary and the twisted uterine tube was evidenced, and adnexectomy was performed (Figure 2). The definitive study certified a spindle cell tumor with changes secondary to tubal torsion. Adnexal torsion is a rare gynecological emergency caused by twisting of the ovary or tube around the infundibulopelvic ligament.1 It often presents acutely as peritoneal pain and irritation requiring urgent surgical intervention.2 However, exceptionally (1: 1.5 million) 3 its clinical presentation is silent (vague abdominal pain, vomiting or palpable mass) being diagnosed late in imaging tests or pathological studies of surgical specimens.1